AN OUTBREAK OF PESTE DES PETITS RUMINANTS IN GOATS AT DISTRICT LAHORE - A. Rashid; M. Asim; A. Hussain (Journal of Animal and Plant Sciences, 2008)
Peste des petits ruminants (PPR) is a highly contagious and economically important disease of small ruminants caused by a virus in the genus morbillivirus, family paramyxoviridae. This infection is responsible for high morbidity and mortality. In this study, an outbreak of PPR in goats was investigated in a well organized farm at district Lahore. Clinical signs, gross lesions and histopathological findings led to the suspicious of outbreak of PPR. Mesenteric lymph nodes and spleen samples collected from the dead animals were found positive for the PPR antigen by agar gel immunodiffusion (AGID) against hyperimmune anti-PPRV serum. Moreover, younger animals were more susceptible to PPR than adults.
Keywords: Peste des petits ruminants; PPR; agar gel immunodiffusion; hyperimmune anti-PPRV serum